Morning-Evening Grave Talqin as a Living Qur’an Practice in the Death Tradition of Nagari Sialang Gaung Community - Jima Erida (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Death-related rituals in Muslim societies often reflect the dynamic interaction between Islamic teachings and local cultural practices. In Indonesia, particularly within Minangkabau society, such traditions are shaped by the integration of religious values and customary norms, creating distinctive forms of lived religious expression. This study aims to examine the practice of morning-evening grave talqin in Nagari Sialang Gaung, Dharmasraya Regency, as a manifestation of the Living Qur’an. Employing a qualitative field research design, the study draws on in-depth interviews and observations involving local religious leaders (urang siak) and family members of the deceased. The findings reveal that the talqin ritual, performed systematically for seven consecutive days after burial, functions not merely as a mortuary tradition but as a medium for embodying Qur’anic values in everyday life. The recitation of Qur’anic verses, supplications, and tahlil serves both as a spiritual effort to seek mercy and tranquility for the deceased and as a mechanism for reinforcing faith, social solidarity, and collective religious awareness among participants. From a Living Qur’an perspective, this practice illustrates how the Qur’an operates as a “living text,” continuously interpreted and enacted within specific socio-cultural contexts. The study contributes to broader discussions on lived Islam by demonstrating how scriptural teachings are negotiated, localized, and sustained through communal ritual practices in response to the existential reality of death.